Improvement of Evaluation of 3-D Characteristics of a Diode-Pumped Alkali Laser - Juhong Han; Xiaoxu Liu; He Cai; Guofei An; Wei Zhang; Hongyuan Wang; You Wang (IEEE Photonics Journal)
It has been proved that a diode-pumped alkali laser (DPAL) is one of the potential candidates to achieve the output power with kW-order or more. However, the theoretical analyses of a DPAL are still incomplete although some regimes have been developed to evaluate the spatial characteristics of a DPAL. It is necessary to build a mathematical model to analyze the tridimensional features of a DPAL system with the much higher output power. By combining the procedures of heat transfer and laser kinetics, we developed a new algorithm to simultaneously evaluate the three-dimensional (3-D) lasing characteristics and the 3-D thermal features of a cesium-vapor laser end-pumped by a laser diode. The 3-D population density distributions of the quasi-five-level of atomic alkali, temperature distribution, and distributions of the absorbed power and laser photon density inside a vapor cell have been systematically obtained and analyzed. The theoretical results of the output characteristics coincide with the experimental ones. The results are thought to be meaningful for the realization of a high-powered DPAL in the future.